Piercing the corporate veil: a review of the concept and considerations of its relevance in South African tax law - Glaser, M (Centre for Law and Society, 2024)
The main objective of this research is to ascertain the degree to which the concept of the corporate veil is relevant in South African Tax Law. The first part of the paper is introductory in nature and is devoted to reviewing the concept from a company law perspective. Part I thus focuses on the following areas: • limited liability - rationale for; history and development, and implications • disregarding the company's separate personality • literature survey pertaining to the United Kingdom, Australia, United States and South Africa. In concluding part I, it is submitted that the dicta of Lord Halsbury in the Salomon case has stood the test of time and still represents the law today. Part II deals with the application of the concept in South African and selected overseas tax cases. It has been found most relevant in relation to the determination of a company's intention and in tax avoidance cases. In addition, part II focuses on specific aspects of gross income and deductible expenditure, as well as some related topics. In many instances, the corporate veil concept is linked to the debate of substance versus form. Over time, it seems that "substance" has gained ground at the expense of "form", particularly in tax avoidance scenarios. In conclusion, it is submitted that the concept is relevant in the tax law context and needs to be considered by tax practitioners dealing with both large and small companies.